Self-Stigma and Mental Health in Divorced Single-Parent Women: Mediating Effect of Self-Esteem - Anna Kim; Sesong Jeon; Jina Song (Behavioral Sciences, 2023)
Numerous studies have addressed the issue of “self-stigma” among divorced single-parent women. However, there is a scarcity of quantitative data available on this subject. Moreover, while self-esteem is a crucial factor throughout life, it has been extensively studied in the context of “children” from single-parent families, but not from the perspective of parents themselves. To address this gap, the present study aimed to explore the relationship between self-stigma, self-esteem, and mental health in 347 divorced, single-parent women. The online survey recruited participants randomly, with a specific focus on single mothers who were divorced and had more than one child under the age of 18. The analysis involved utilizing SPSS 25.0 (IBM Co., Armonk, NY, USA) and PROCESS Macro Version 4.1 (Model 4) to conduct descriptive statistics, frequency analysis, reliability assessment, correlation analysis, and mediating analysis. The findings revealed that self-esteem played a partial mediating role in the relationship between self-stigma and mental health. In other words, higher levels of self-stigma among divorced, single-parent women were associated with poorer mental health outcomes. Additionally, the study discovered that engaging in more self-stigma was linked to lower self-esteem and increased mental health distress. These results underscore the significance of internal factors, such as self-stigma and self-esteem, and highlight their relevance in formulating policies aimed at supporting divorced single-parent women. Policymakers should take these factors into account to develop effective strategies to aid this specific group.